PENGARUH KOMPETENSI DAN INDEPENDENSI PADA KINERJA AUDITOR DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Yadnya, Putu Parta; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
The study aims to determine the effect of variables on the performance competence and independence of auditors with auditor ethics as a moderating variable. Data obtained in the form of primary data from (KAP) throughout Bali that are already registered in the (IAPI) in 2015 which is entirely located in the city of Denpasar. Elections were conducted with a purposive sampling method, so it was chosen by 46 respondents. In this case the researchers came to direct the public accounting firm and provides direct questionnaires. The test results showed that together (simultaneously) variable competence, independence and ethics auditor significant effect on the performance of auditors, while partial competence variable significant effect on the performance of auditors, variable independence significant effect on the performance of auditors, ethics auditor strengthen the relationship between the competence of the performance auditor, auditor ethics strengthen the links between the independence of the auditor performance.
Keywords: competence, independence, ethical auditors, the performance auditor